Giese-type alkylation of dehydroalanine derivatives via silane-mediated alkyl bromide activation - Perry van der Heide; Michele Retini; Fabiola Fanini; Giovanni Piersanti; Francesco Secci; Daniele Mazzarella; Timothy Noël; Alberto Luridiana (Beilstein Journal of Organic Chemistry)
The rising popularity of bioconjugate therapeutics has led to growing interest in late-stage functionalization (LSF) of peptide scaffolds. α,β-Unsaturated amino acids like dehydroalanine (Dha) derivatives have emerged as particularly useful structures, as the electron-deficient olefin moiety can engage in late-stage functionalization reactions, like a Giese-type reaction. Cheap and widely available building blocks like organohalides can be converted into alkyl radicals by means of photoinduced silane-mediated halogen-atom transfer (XAT) to offer a mild and straightforward methodology of alkylation. In this research, we present a metal-free strategy for the photochemical alkylation of dehydroalanine derivatives. Upon abstraction of a hydride from tris(trimethylsilyl)silane (TTMS) by an excited benzophenone derivative, the formed silane radical can undergo a XAT with an alkyl bromide to generate an alkyl radical. Consequently, the alkyl radical undergoes a Giese-type reaction with the Dha derivative, forming a new C(sp3)–C(sp3) bond. The reaction can be performed in a phosphate-buffered saline (PBS) solution and shows post-functionalization prospects through pathways involving classical peptide chemistry.